2007
DOI: 10.1089/ast.2006.0097
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Analysis of Halophilic Archaea by Resonance Raman Spectroscopy

Abstract: Recently, halite and sulfate evaporate rocks have been discovered on Mars by the NASA rovers, Spirit and Opportunity. It is reasonable to propose that halophilic microorganisms could have potentially flourished in these settings. If so, biomolecules found in microorganisms adapted to high salinity and basic pH environments on Earth may be reliable biomarkers for detecting life on Mars. Therefore, we investigated the potential of Resonance Raman (RR) spectroscopy to detect biomarkers derived from microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
101
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 25 publications
5
101
0
3
Order By: Relevance
“…In this way, trace pigment detection is sometimes possible using especially the excitation wavelengths 514.5 and 532 nm [12][13][14]. Carotenoids can also be identified in native samples from surface or subsurface colonizations of rocks or sediments using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, trace pigment detection is sometimes possible using especially the excitation wavelengths 514.5 and 532 nm [12][13][14]. Carotenoids can also be identified in native samples from surface or subsurface colonizations of rocks or sediments using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The first type refers to non-compound specific or conventional water quality sensors, which are normally used for routine water quality parameters, including pH, chlorine, total organic carbon (TOC), oxidation reduction potential (ORP), conductivity and temperature. The second type refers to compound specific water quality sensors or advanced sensors, which are capable of confirmative detection at low concentrations for a specific component [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Marshall et al (2007) reported on the identification of carotenoids in halophilic archaea by resonance Raman spectroscopy using 514.5 nm excitation wavelength. The choice of this excitation wavelength is useful when analysing carotenoids owing to its coincidence with an electronic transition in the chromophore portion of carotenoids (p-p * ) resulting in the Raman resonance effect, thus significantly enhancing the Raman signal.…”
Section: Introductionmentioning
confidence: 99%